Effect of Ti content on microstructure and mechanical properties of SiCf/SiC composites/GH536 superalloy joints brazed with CoFeCrNiCuTi high entropy filler. (6th January 2023) - Zhao, Shuai; Chen, Haiyan; Nai, Xin; Wang, Peng; Deng, Huai; Wen, Guodong; Liu, Fenjun; Li, Wenya
Abstract: In this study, SiCf /SiC composite and GH536 superalloy was successfully vacuum brazed with a self-made CoFeNiCrCuTix high entropy filler with different Ti content. The effect of Ti content in the brazing fillers on the microstructure and mechanical properties of joints was studied in detail. When the molar ratio of Ti element to the elements in the filler is 0.5, the typical interfacial microstructure of joint is SiCf /SiC/Cr23 C6 /TiC/Ti3 SiC2 /TiNi3 /Ni2 Si/Fe3 Si/MoNiSi/HEAF/rich-Ni phase/GH536. Increasing Ti content in the filler, the interfacial reaction controlled by Fe and Ni elements is gradually dominated by Ti elements. The TiC phase distributed in the form of continuous strips inhibits and reduces the generation of brittle phases FeSi and NiSi, which is beneficial to improve the mechanical properties of joints. The maximum shear strength of the brazed joint reach 98.23 MPa when the molar ratio of Ti content to other elements in the filler is 1, which is 14.10 % higher than that obtained using filler without Ti element. This work proves that Ti element in high entropy fillers can regulate interfacial reactions and reduce the amount of brittle intermetallic compounds, thus providing a new idea for high entropy filler design and its application in the field of brazing. Graphical abstract: Unlabelled Image Highlights: SiCf /SiC composite and GH536 were brazed by CoFeNiCrCuTix filler successfully. The diffusion of Ni and Fe elements can be effectively blocked by TiC layer. The maximum shear strength of brazed joint was up to 98.23 MPa. A physical model was proposed to describe the microstructure evolution.